Hanafi School of Islamic Law Perspective on the Implementation of Rice Field Pawning - Ahmad Maza Atiqur Rohman; Muhammad Hamdi; Syara Pasaribu (Jurnal Informatika Ekonomi Bisnis, 2026)
This research aims to examine the implementation of rice field pawn practices in Wringinagung Village, Jombang District, through the perspective of Hanafi Islamic jurisprudence. The study is motivated by the continued existence of rice field pawning among rural communities as a form of informal financial solution to fulfill urgent economic needs. In its implementation, the management rights over the rice fields are transferred to the creditor until the debt is fully repaid, while the agricultural yields are utilized by the creditor. This study applied a qualitative field research method using juridical-normative and sociological approaches. Primary data were collected through interviews with rahin, murtahin, and local community leaders, while secondary data were obtained from Hanafi fiqh literature, academic journals, and other related references. Data collection techniques involved interviews, observation, and documentation, followed by descriptive-analytical analysis. The findings reveal that the practice of rice field pawning in Wringinagung Village is predominantly based on mutual trust and customary traditions without written agreements or clear time limitations. From the Hanafi fiqh perspective, the rahn contract is legally permissible; however, the use of pawned property by the creditor should not result in injustice or unilateral benefit. The absence of clear contractual arrangements and the full utilization of harvest yields by the creditor may contradict the principles of justice and legal certainty in Islamic law. Therefore, improvements in the implementation mechanism are necessary so that rice field pawning practices align with the values of justice, public benefit, and sharia principles.